2022
DOI: 10.1371/journal.pone.0276000
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and predictive factors of severe or fatal suicide outcome in patients hospitalized due to deliberate self-poisoning

Abstract: Prediction of clinical course of intoxication is essential for timely initiation of appropriate medical treatment in patients hospitalized due to suicidal self-poisoning. In this retrospective single-centre study in patients hospitalized due to suicidal poisoning in a specialized clinical toxicology unit, we aimed to identify predictive factors associated with severe or fatal course of self-poisoning. All patients underwent at least one psychiatric exploration during their inpatient stay. Severity of poisoning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…[6,18,19] The identification and treatment of poisoned people can be extremely difficult in the absence of clinical experience. [6,[20][21][22] Regional poison centers have been set up in a number of nations to address this problem and provide poisoned patients with expert care. [23][24][25][26][27][28][29][30] Poison centers have just recently been established in China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6,18,19] The identification and treatment of poisoned people can be extremely difficult in the absence of clinical experience. [6,[20][21][22] Regional poison centers have been set up in a number of nations to address this problem and provide poisoned patients with expert care. [23][24][25][26][27][28][29][30] Poison centers have just recently been established in China.…”
Section: Discussionmentioning
confidence: 99%
“…This differs from the typical scenario of acute poisoning, where the majority of cases are attributed to suicide. [21,28,30] The disparities among poisoning populations can account for this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Although male sex was previously identified as a determinant of admission to critical care among self-poisoned patients who attempted suicide [7,8], we did not confirm this finding and observed that patient sex was not a determinant of admission to critical care in presentations to the ED with acute recreational drug toxicity. A recent retrospective single-center study at a specialized clinical toxicology unit showed that male sex increased the odds of a severe course of self-poisoning with suicidal intention [16], confirming the evidence that suicide-related behaviors in males, including self-poisoning, are often characterized by a more serious outcome [17][18][19]. Conversely, with regard to drug use for recreational purposes, a previous study by Miro et al within the Euro-DEN Plus database showed that when the admission to critical care was considered a marker of severity of acute recreational drug toxicity, no sex differences emerged from regression analyses adjusted by age, regardless of the type and number of drugs used [20].…”
Section: Determinants Of Admission To Critical Carementioning
confidence: 99%
“…The accessibility of these agents, influenced by factors such as lax regulations and easy availability, contributes to their frequent use in intentional self-poisoning. Recognizing the patterns of substance use is vital for implementing targeted preventive measures, including stricter control over access to potentially harmful agents and educational initiatives on the risks associated with specific substances [15][16][17]. The reported 14% of participants with a history of previous suicidal attempts aligns with a meta-analysis by Hawton et al [18], indicating that a history of selfharm is a significant predictor of future attempts.…”
Section: Socioeconomic Factorsmentioning
confidence: 62%